Educational sustainability initiatives in higher education: An integrative approach to urban areas in northwestern Portugal - Hélder Silva Lopes (Societal Impacts)
This paper explores the integration of sustainability and climate change education within Higher Education (HE), emphasizing the societal impact of such initiatives. Through a comprehensive analysis of various educational projects conducted between 2020 and 2024 in Portugal, the research highlights the critical role of education in fostering sustainable development and resilience to Climate Change (CC). Utilizing a participatory-based methodology, including the TIP (Territory, Intervention, Proposal) model, the study involved collaboration among students, experts, and local stakeholders to address urban and environmental challenges. The findings underscore the importance of embedding sustainability into educational frameworks to equip students with the necessary knowledge and skills to tackle complex environmental issues. Moreover, the projects demonstrated how HE institutions can act as catalysts for societal change, aligning with Sustainable Development Goals (SDGs) and promoting a multidisciplinary approach. Future research should focus on evaluating the long-term impacts of these educational practices on fostering sustainable behaviors in young people and local communities, crucial agents of change in the face of climate change.